2021
DOI: 10.1016/j.apcatb.2021.120333
|View full text |Cite
|
Sign up to set email alerts
|

Pt/CeO2 with residual chloride as reusable soft Lewis acid catalysts: Application to highly efficient isomerization of allylic esters

Abstract: Heterogeneous acid and base catalysts play a crucial role in many important chemical processes. Hard Lewis and Brønsted acid catalysts like silica-alumina and zeolites have been widely applied in numerous reactions; however, developing reusable and active soft Lewis acid catalysts remain a challenge. Herein, we demonstrate for the rst time that a highly dispersed supported platinum catalyst can act as a heterogeneous soft Lewis acid. High turnover numbers and reusability were observed in the isomerization of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…A recent study has showed that 3,4-diacetoxy-1-butene (diester of 3-butene-1,2-diol) can be isomerized to the equilibrium mixture of diacetoxybutenes over noble metal catalysts such as Pt/CeO 2 . [64] However, our results of the reaction of cis-2-butene-1,4-diol with very low selectivity to 3-butene-1,2-diol rather suggested the direct conversion to 1,3-butadiene without initial isomerization to 3-butene-1,2-diol. Then, we carried out density functional theory (DFT) calculation of the reactions of butenediols, erythritol, and 1,2-butanediol over the surface of reduced ReO x /CeO 2 , which is the main active site for DODH reaction (Table S8 and Figure S2; calculation details and the results are described in the Supporting Information).…”
Section: Resultsmentioning
confidence: 54%
“…A recent study has showed that 3,4-diacetoxy-1-butene (diester of 3-butene-1,2-diol) can be isomerized to the equilibrium mixture of diacetoxybutenes over noble metal catalysts such as Pt/CeO 2 . [64] However, our results of the reaction of cis-2-butene-1,4-diol with very low selectivity to 3-butene-1,2-diol rather suggested the direct conversion to 1,3-butadiene without initial isomerization to 3-butene-1,2-diol. Then, we carried out density functional theory (DFT) calculation of the reactions of butenediols, erythritol, and 1,2-butanediol over the surface of reduced ReO x /CeO 2 , which is the main active site for DODH reaction (Table S8 and Figure S2; calculation details and the results are described in the Supporting Information).…”
Section: Resultsmentioning
confidence: 54%
“…In addition, the increase in surface area after modification with GO could be due to the reduction of oxygen containing functional groups on GO surface. 50 Meanwhile, after decoration with Pt nanoparticles on GO–Ce x O y , the surface area decreased, which could be due to blocking of the pores. 51,52 In addition, the increase in the surface area of GO after decoration with Ce x O y is due to disorder in the structure of the GO surface.…”
Section: Characterization Of the Go–cexoy–pt Catalystmentioning
confidence: 99%
“…Platinum-group-metals (PGMs) on oxide supports serve as active sites in heterogeneous catalysts with applications ranging from three-way catalysts to oil rening. [1][2][3][4][5][6][7][8] The cost and scarcity of PGMs require that the metals should be nely dispersed on oxide supports to maximize metal utilization efficiency. CeO 2 is a widely used support material, 9 because PGM dispersions of 100% can be obtained on CeO 2 .…”
Section: Introductionmentioning
confidence: 99%